Regional Right Ventricular Function Assessed by Intraoperative Three-Dimensional Echocardiography Is Associated With Short-Term Outcomes of Patients Undergoing Cardiac Surgery - Keller, Marius; Duerr, Marcia-Marleen; Heller, Tim; Koerner, Andreas; Schlensak, Christian; Rosenberger, Peter; Magunia, Harry (Frontiers in Cardiovascular Medicine, 2022)
Background: The assessment of right ventricular (RV) function in patients undergoing elective cardiac surgery is paramount for providing optimal perioperative care. The role of regional RV function assessment employing sophisticated state-of-the-art cardiac imaging modalities has not been investigated in this cohort. Hence, this study investigated the association of 3D echocardiography-based regional RV volumetry with short-term outcomes. Materials and Methods: In a retrospective single-center study, patients undergoing elective cardiac surgery were included if they underwent 3D transesophageal echocardiography prior to thoracotomy. A dedicated software quantified regional RV volumes of the inflow tract, apical body and RV outflow tract employing meshes derived from 3D speckle-tracking. Echocardiographic, clinical and laboratory data were entered into univariable and multivariable logistic regression analyses to determine association with the endpoint (in-hospital mortality or the need for extracorporeal circulatory support). Results: Out of 357 included patients, 25 (7%) reached the endpoint. Inflow RV ejection fraction (RVEF, 32±8% vs. 37±11%, p=0.01) and relative stroke volume (rel. SV) were significantly lower in patients who reached the endpoint (44±8 vs. 48±9%, p=0.02), while the rel. SV of the apex was higher (38±10% vs. 33±8%, p=0.01). Global left and right ventricular function including RVEF and left ventricular global longitudinal strain did not differ. In univariable logistic regression, tricuspid regurgitation grade ≥2 (odds ratio (OR) 4.24 (1.66-10.84), p<0.01), inflow RVEF (OR 0.95 (0.92-0.99), p=0.01), inflow rel. SV (OR 0.94 (0.90-0.99), p=0.02), apex rel. SV (OR 1.07 (1.02-1.13), p<0.01) and apex to inflow rel. SV. ratio (OR 5.81 (1.90-17.77), p<0.01) were significantly associated with the endpoint. In a multivariable model, only the presence of tricuspid regurgitation (OR 4.24 (1.66-10.84), p<0.01) and apex to inflow rel. SV. ratio (OR 6.55 (2.09-20.60), p<0.001) were independently associated with the endpoint. Conclusions: Regional RV function is associated with short-term outcomes in patients undergoing elective cardiac surgery and might be helpful for optimizing risk stratification.